Unemployment persistence in Argentina. Micro and macroeconomic analysis of its regional incidence - Féliz, Mariano (World Economic Forum.)
The aim of this paper is to develop a simple methodology for the study of regional unemployment persistence in Argentina. We use two complementary perspectives, combining a macroeconomic (aggregate) hysteresis approach with a microeconomic dynamic (individual-two-stage) evaluation. Macroeconomic results indicate that most of the shocks affecting the unemployment rate in different regions and population sub-groups are predominantly persistent (because both participation and mainly em- ployment hysteresis). On the other hand, the microeconomic analysis allow us to detect a strong state-dependence effect (for most regions and mainly for young people and women), while duration-dependece is only significative for high unemployment periods